2020
DOI: 10.36965/ojakm.2020.8(2)91-106
|View full text |Cite
|
Sign up to set email alerts
|

Learning soft skills in the digital age: Challenges and insights from development and teaching 'Negotiation Management' MOOC

Abstract: Massive Open Online Courses (MOOCs), growing in number in recent years, occupy a significant place as an open educational resource, and provide insights into the development process as well as offer an innovative educational experience. This reflective article examines insights gathered during the development and offering of two sessions of a Negotiation Management MOOC. The article reviews the development process of the course which is built as a series of situations that simulate real-life moments. The episo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Banupriya (2011) referred to soft skills as "cluster of personality traits, social graces, facility with language, personal habits, friendliness, and optimism that marks each of us to varying degrees" (p. 109). Kopolovich (2020) defined soft skills as "non-technical skills, enable individuals to interact effectively and cooperatively with others" (p. 92). Dash et al (2020) showed that soft skills are related to language learning, concepts of behavioral aspects, and grooming etiquette for better employability.…”
Section: Language Learning and Soft Skill Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Banupriya (2011) referred to soft skills as "cluster of personality traits, social graces, facility with language, personal habits, friendliness, and optimism that marks each of us to varying degrees" (p. 109). Kopolovich (2020) defined soft skills as "non-technical skills, enable individuals to interact effectively and cooperatively with others" (p. 92). Dash et al (2020) showed that soft skills are related to language learning, concepts of behavioral aspects, and grooming etiquette for better employability.…”
Section: Language Learning and Soft Skill Developmentmentioning
confidence: 99%
“…They have described how different soft skills can be implemented in foreign language training, including communication skills, teamwork skills, presentation skills, negotiation skills, leadership skills, and intercultural skills. Kopolovich (2020) proposed the development of a soft skill MOOC with the title "Negotiation Management" for teaching soft skills and stressed the importance of teaching soft skills via MOOCs. Cinque (2017) showed how MOOCs can help in training 21st century skills including both soft skills and digital soft skills.…”
Section: Language Learning and Soft Skill Developmentmentioning
confidence: 99%